On the distributional effects of minimum wages: A note - Friedrich L. Sell; Michael Öllinger (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2017)
In this note, we recall that unions traditionally pursue a policy of pushing higher average wages and, at the same time, for a compression of the structure of wages and salaries, which is some sort of equity. Given the precipitous fall of union density in many, if not all, OECD countries, the actual good climate for minimum wage policy comes at no surprise. Despite the fact that unions do dislike the intervention of labor market policy to the detriment of tariff autonomy, we can show that minimum wages are capable of serving both of the above-mentioned goals of unions and also help increase the overall wage quota in the economy. Hence, It can be concluded that the unions have a double dividend when inviting policy makers to pursue a policy of minimum wages: both the average wage rate can be increased and the dispersion of wages be lowered, ceteris paribus.
Keywords: J51; J38; J41; J58; 330; strategy of unions; wage dispersion; average and minimum wages; wage quota